Gaya Mengajar Interaksional Yesus Sebagai Pola Dalam Menyampaikan Firman Tuhan Di Sekolah Minggu - Lidya Octavia Samosir; Pestaria Happy Kristiana (Sekolah Tinggi Teologi Injili Indonesia Bali, 2023)
This research is aimed at providing exposure to educators, in this case Sunday school teachers, about Jesus' interactional teaching style. It is hoped that by understanding Jesus' interactional teaching style, Sunday school teachers can be more effective in conveying the truth of God's Word. This research is important, considering that the aim of conveying God's Word is life change. However, this goal has not been achieved optimally. This is because individual educators do not understand teaching styles that can make the learning process in Sunday school more interesting and effective. To find this teaching style, researchers used qualitative research methods with literature studies and expositions from the Gospels about Jesus' teaching style. There are 5 principles of Jesus' interactional teaching style, namely: Dialogue, two-way delivery, situational problems, dominant role of students and teachers as facilitators.